(untitled) (Eurasian Medical Research Periodical, 2026)
Acute calculous cholecystitis (ACC) is the second most common surgical emergency of the abdominal cavity. Despite advances in laparoscopic technique, the rate of destructive forms and associated complications remains substantial, largely because decisions regarding operative timing rely on subjective clinical criteria. Genetic polymorphisms governing inflammatory response, angiogenesis, and antioxidant defence may predetermine individual susceptibility to rapid gallbladder wall destruction; however, their clinical significance in the Uzbek ethnic population of the Fergana Valley has not previously been investigated.